Are Exports, Imports, and Exchange Rates Cointegrated? Empirical Evidence from Nepal - Devkota, Mitra Lal; Panta, Humnath (International Journal of Economics and Financial Issues, 2019)
This paper attempts to empirically investigate the presence of a cointegrating relationship between the exports, imports, and the USD exchange rate in Nepal using the yearly time series data from 1965 to 2017. Time series properties of the data are diagnosed using the Augmented Dickey-Fuller unit root test and Johansen’s multivariate cointegration test. The findings indicate that there exists no cointegrating relationship between exports, imports, and the USD exchange rate in Nepal, and hence, no causal relationships within vector error correction model (VECM) can be estimated for Nepal. The lack of cointegration implies that macroeconomic policies of Nepal have been ineffective in bringing exports and imports in long-run equilibrium, and thus, Nepal is in violation of her international budget constraint. These findings may have important implications for decision- making by national policymakers. Keywords: Exports, Imports, International Budget Constraint JEL Classifications: F41, C22, C32 DOI: https://doi.org/10.32479/ijefi.7588